Modeling and optimization of supply chain cost of responsiveness - Ahmed, Moataz Mohamed Magdy Hamouda (AUC Knowledge Fountain, 2010)
In today's ever increasing competitive business world, a responsive Supply Chain (SC) should adapt itself quickly to customer demands resulting into maximum benefits to all its primary stakeholders. The objective of this work is to provide a managerial tool that optimizes the cost of responsiveness of supply chains where various transportation durations are present between the SC components, and to determine the weakest links in the SC that need strengthening for elevating the overall responsiveness. For these objectives a mathematical model was formulated and solved using CPLEX. Assessing supply chain's responsiveness is discussed in this work as well using the cost of responsiveness, SC output rate and production slack times. The computational results show that the mathematical model is effective in planning and synchronizing production, shipping and storage in a supply chain from start to end so that the cost of responsiveness is minimized while customer demands are fulfilled under limited outsourcing.